Remedial instuctional techniques : assessing the effectiveness of high imagery teaching techniques in the remedial environment. - Ravenscroft, Gregg (My University, 2009)
The primary focus of this research is to establish whether there is improvement in the reading, writing and spelling skills of learning disabled children, where high imagery teaching techniques are used for remediation. The results of seventeen small-scale studies were combined using aggregative case survey methodology to form a sample of 93 children (63 treatment and 30 control). Analysis indicated that children in both conditions made similar gains in phonic skills. However a significant difference in scholastic skills for children who received high imagery instruction was noted in comparison to those who received structured phonics. Overall, the results would suggest that high imagery teaching techniques may be an alternative remediation strategy to structured phonic techniques; especially where children are not making progress in the latter. The results also indicate that progress is made regardless of gender, age, grade at school, extent of the child’s learning deficit / developmental lag or level of visualisation ability.
Keywords: Remedial teaching